Perfil de la secretaria y su incidencia en la calidad de servicio y atención al usuario - Jimenez Sandoya, Tatiana Carolina (2020)
The present case study was made with the theme : Profile of the Secretariat and its incidence in the quality of service and attention to the user. The proof that the assistant in charge of that department must meet a professional profile, to be able to efficiently make all their activities, were limiting, even the idea was, that she was only responsible for preparing coffee to their superiors and answer the phone. Currently the role of the secretary has evolved involved in income in decision-making in the organization. You must be with a series of qualities and individuals, is able to respond, you will be able to evolve in your occupation in the most splendid way and also cooperate with different friendships as a delegation of a group of co-worker. It is the habit developed and practiced by an organization to interpret the needs and expectations of its customers and to offer them, consequently, an accessible, adequate, agile, flexible, appreciable, useful, appropriate, safe and reliable, still under unrest and existing errors, in such a way that the client sits understood, careful and served personally, with dedication and efficiency, and surprised with greater value to the expected, in consequence, more income and small costs for the organization.